Online Chemistry Learning Management Model Promoting Students’ Scientific Communication in the Special Program Classroom on Science, Mathematics, and Technology, and Environment during the Pandemic Covid-19 Situation - Fakngern, Supak; Chapoo, Suriya; Chanunan, Skonchai (Asia Research Network Journal of Education, 2022)
The purpose of this qualitative research is to study the opinions of five Chemistry teachers towards online Chemistry learning management model that has promoted students’ scientific communication in the special program classroom on Science, Mathematics, and Technology and Environment during the pandemic Covid-19 situation. The data are collected by a semi-structured interview. The content analysis is conducted to analyze the data and verified with the interviewees and the experts. The findings reveal that the online Chemistry learning management model 1) the online Chemistry learning management model is the 5 E’s of Inquiry-Based Learning according to the Institute for the Promotion of Teaching Science and Technology, 2) this online learning management based on the 5 E’s of Inquiry-Based Learning has developed students to achieve their learning objective on the knowledge about the content and developed their 21st century core skills, 3) this management based on the 5 E’s of Inquiry-Based Learning has promoted 3.1) critical thinking skill and problem-solving skill, 3.2) computer and information technology and communication skill, and 3.3) collaboration, teamwork and leadership skill, 4) the online learning management promoting scientific communication are 4.1) the 5 E’s of Inquiry-Based Learning and 4.2) Active Learning, and 5) some technologies integrated in this online learning management promoting scientific communication are Google meet, Google site, Zoom, Flip classroom, Padlet, and Google Jamboard.